21st Century Instructional Leadership and Strategic Management of Technical Vocational Education and Training Programs - S. Cabreros, Bryan (Journal of Technical Education and Training, 2023)
The present study attempted to examine the relationship between 21st-century leadership and strategic management of school principals concerning their strategy formulation, implementation, and evaluation. This is with an end-view of preparing actions and activities to help strengthen their leadership skills in the 21st-century era. The study is descriptive-correlational in nature, employing a survey questionnaire responded to by 80 TLE teachers from public secondary schools in Districts II and V of Batangas Province. Quantitative analysis indicated that concerning the 21st-century leadership skills of TLE teachers, they generally agree that their school heads manifest strong advocacy and leadership (3.45) while they strongly agree that they display adult professional core (3.52), continuous improvement of teaching expertise (3.50), and results-oriented team (3.51). In terms of the strategic management of TVET programs during this time of the pandemic, they agree that their school heads employ various strategies for strategy formulation (3.36), strategy implementation (3.40), and strategy evaluation (3.41). Pearson’s R correlation revealed a moderate to very high correlation between strong advocacy and leadership, adult professional core, continuous improvement of teaching expertise, and results-oriented teams with their strategic management of the school heads. It was therefore suggested that school heads explore and initiate actions that will help foster their 21st-century leadership skills as it was found that it is influential in the strategic management of the TVET programs, particularly during this time of global health emergency.